Linking supply chain social capital factors, supply chain integration strategy and operational performance in the Malaysian food processing industry / Zurita Mohd Saleh - Mohd Saleh, Zurita (2016)
The food processing industry has become a significant contributor to Malaysia's socio-economy and is also an important source of employment. However, lately, this industry has been experiencing problems in terms of its fragmented supply chain system, lack of latest technology adoption, sub-standard grades of raw materials and low product innovation. Furthermore, this industry is often associated with poor understanding and execution of best business practices. The current business environment has witnessed increased competition from foreign food companies having the same entry opportunities in the local market whilst many of the Malaysian food processing companies find it difficult to penetrate overseas market. To a large extent this is because of aggressive competition from the counterparts in Thailand, Indonesia and China, who have already established their presence globally and are more receptive to market changes. Existing studies have established that supply chain is the key towards competitive ability. In view of this, there is a need to investigate the supply chain integration strategy (SC integration strategy) between the food manufacturers and their supply chain partners both internally and externally. This study focuses on how to improve the operational performance of the food processing industry. It analyses the integration strategy between food manufacturers and its supply chain partners to allow for greater understanding in the field of supply chain management (SCM). Drawing upon the Supply Chain Management (SCM)perspectives and Social Capital Theory, this study evaluates the relationships between critical constructs; Supply chain (SC) structural, Supply chain (SC) relational, Supply chain (SC) cognitive, Supply chain (SC) integration strategy and operational performance. This study intends to shed lights into the potential of supply chain integration in establishing effective supply chains of food processing. Based on this premise, the objectives of the study are to establish a link between the main independent constructs of social capital, SC integration strategy and operational performance and their dimensions as well as to examine the mediating role of SC integration strategy. This study contributes to knowledge by examining the presence of the social capital constructs as enablers and the influence of SC integration strategy. Data for this study was gathered through a mail survey of food processing manufacturers utilizing the questionnaire as the instrument. A total of 184 food processing manufacturers participated in the survey. The analysis used the PLS path modelling approach by examining the mediating effects of SC integration strategy. The findings reveal that each of the main social capital constructs has positive and significant effects on SC integration strategy. However, one of the social capital main constructs, SC structural as represented by IT management and IT technical infrastructure, did not demonstrate significant relationship on operational performance. Importantly, this study provides empirical evidence that SC integration mediates the relationship between individual SC social capital construct and operational performance. This finding is consistent with the movement of the industry players towards implementing 'best practices' that emphasized on SC integration. Following these findings, a number of implications are offered for the food processing industry. The food industry players should invest on soft behavioural aspects and adopt SC integration strategy in order to enhance their performance particularly in the operational perspectives of supply chain management.